The Relationship between Knowledge, Attitudes and Subjective Norms with Parents' Intentions in Preventing Early Marriage in Genting Juar Village, Semidang Alas Maras District, Seluma Regency - Oka Apri Sinta; Fitriani Mediastuti; Gunarmi (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Early marriage is prevalent in various regions of Indonesia and is a health, social, and educational issue that requires attention. Teenagers who marry at an early age are at risk of reproductive health problems, impaired child development, dropping out of school, and limited future economic opportunities. Furthermore, the decision to marry off a child is often influenced by parental knowledge, attitudes toward early marriage, and subjective norms prevailing within the family and community. Therefore, research on early marriage is needed to identify factors influencing parental intentions to prevent the practice, thus providing a basis for designing more targeted interventions and prevention programs. Objectives: This study aims to determine the relationship between knowledge, attitudes and subjective norms with parental intentions in preventing early marriage in Genting Juar Village, Semidang Alas Maras District, Seluma Regency. Methods: This research is an analytical survey with a cross-sectional approach. The study population was all parents with teenage daughters in Ganting Juar Village, Semidang Alas Maras District, Seluma Regency. The sampling technique used total sampling, totaling 100 respondents. Univariate and bivariate data analysis used the Chi-Square test and Logistic Regression test. Results: The results of the study showed that the calculated F value was 15.322 with a significance level of 0.000 (<0.05). This indicates that the independent variables simultaneously have a significant effect on the dependent variable. Conclusions: There is a relationship between knowledge, attitudes and subjective norms with parents' intentions to prevent early marriage